Serum Concentrations of Gastrin after Famotidine and Omeprazole Administration to Dogs - Parente, N.L. (J Vet Intern Med, 2014)
BACKGROUND: The duration of antacid‐induced hypergastrinemia after cessation of administration of omeprazole and famotidine apparently has not been determined in dogs. HYPOTHESIS: That serum gastrin will return to basal concentrations by 7 days after cessation of famotidine or omeprazole administration. ANIMALS: Nine healthy, adult, male, research colony dogs. METHODS: Randomized, cross‐over design. Serum gastrin was determined daily for 7 days to establish baseline concentrations. Famotidine (1.0 mg/kg q24h) or omeprazole (1.0 mg/kg q24h) was administered PO for 7 days followed by a 14‐day washout. Serum concentrations of gastrin were determined daily during 7 days of administration and daily for 7 days after cessation of administration. Each drug was evaluated in 8 of the 9 dogs. RESULTS: Omeprazole caused a significant increase in serum gastrin concentration (37.2 ± 7.3 to 71.3 ± 19.0 ng/L; P = .006). Famotidine induced a transient increase in serum gastrin (37.2 ± 7.3 to 65.5 ± 38.5 ng/L; P = .02) that peaked at administration day 3 and declined thereafter. By day 7 after cessation of both drugs, there was no difference in serum gastrin concentrations compared to those before administration (famotidine P = .99; omeprazole P = .99). During or after administration, gastrin concentrations above 3 times the upper reference range were rare (12 of 224 samples). CONCLUSIONS AND CLINICAL IMPORTANCE: A 7‐day withdrawal from short‐term administration of famotidine or omeprazole is sufficient for serum gastrin to return to baseline concentrations. Withholding famotidine or omeprazole for longer before investigating pathologic causes of hypergastrinemia is unnecessary.